Investeringscultuur in Nederland: Ruraal beleggingsgedrag in een burgerlijk-stedelijke samenleving, 1780-1880 - Brusse, Paul (TSEG - The Low Countries Journal of Social and Economic History, 2022)
Rural investment cultures in a town-based bourgeois society This article is about the investment behaviour of the elite in the Netherlands between 1780 and c.1880. According to the literature, at that time, the Dutch invested their capital mainly in securities. This paper shows, however, that investment behaviour in the city, i.e. Amsterdam, differed from investment behaviour in the countryside, i.e. the provinces of Gelderland and Overijssel. It argues that these differences were culturally determined and that, in this context, it is more accurate to speak of investment culture. Moreover, this paper states that the investment culture of the rural elite was less conservative than that of the urban elite and that this is an indication that the countryside was emancipating from the city.